Language Exposure and Writing Ability : A Correlational Study in English Learning Context: A Correlational Study of Eighth Grade Students in the 2024/2025 Academic Year - Lusyani Mardiyanti Nur; Lena Sastri; Absharini Kardena; Elsi Amiza (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This research investigated the correlation between students’ language exposure and their writing ability. It was motivated by several issues identified among students, such as difficulties in expressing ideas effectively, inconsistencies in writing styles possibly influenced by different levels of language exposure, and a lack of familiarity with proper writing structures. The objective of this research was to determine whether there is a significant correlation between students’ language exposure and their writing ability among eighth-grade students. A correlational research design was employed in this research. The population consisted of 80 eighth-grade students, and total sampling was used to include all participants. The instruments used were a questionnaire and a writing test. The questionnaire contained 23 items to measure students’ language exposure, while the writing test required students to write a recount text based on one of four given topics. The data were analyzed using the Pearson Product Moment correlation through SPSS. The findings revealed a correlation coefficient of 0.755, indicating a strong and positive relationship between students’ language exposure and their writing ability. The results suggest that greater exposure to the English language significantly contributes to the improvement of students’ writing ability. It can be concluded that enhancing students’ engagement with English through various forms of exposure plays an important role in developing their writing proficiency.